A typology of foreign auction markets in sub-Saharan Africa. - Aron, J; Elbadawi, I (World Bank, 1994)
The authors compare and contrast the design and outcomes of different foreign exchange auctions in four countries in sub-Saharan Africa and present a typology of such auctions. They identify two distinct sets of countries in terms of the auctions' features, policy interventions, and outcomes. In Ghana and Uganda, the exchange rate auctions are judged to have been largely on target in exchange rate unification, exchange rate stabilization, and efficient allocation of foreign exchange. The auctions in Nigeria and Zambia, on the other hand, were subject to frequent policy interventions, resulting in unsustainable auctions, inefficient allocation of foreign exchange (through ad hoc disqualifications), limited unification, and a rather volatile exchange rate. The conclusions reached by the authors are broadly corroborated by a statistical analysis of weekly micro-auction data for all four countries.